EXPLORING THE CULTURAL COGNITION AND THE CONCEPTUAL METAPHOR OF MARRIAGE IN INDONESIA - Kusmanto, Joko (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
This paper explores what cultural cognition of ‘marriage’ is metaphorically conceptualized in Indonesian expressions. This paper has two questions. Firstly, what cultural cognitions of ‘marriage’ are encoded in the use of metaphorical expressions in Indonesian? Secondly, how such cultural cognition of ‘marriage’ is metaphorically conceptualized in Indonesian expressions? The analysis and discussion of this exploration basically follow (i) the principles of embodiment in Cognitive Linguistics and (ii) the logic of cultural conceptualization in Cultural Linguistics. Both serve as the primary bases to analyze the problem of the study. The paper is expected to contribute to the present linguistic study in two-fold benefits. Firstly, it presents the discussion of the cultural cognitions of marriage represented in Indonesian metaphorical expressions. Secondly, it discusses the methodological issues of (i) how to understand the relation between culture and language and (ii) how to uncover any cultural representations in linguistic metaphors.